Political Development of Women in Nigeria, 1985-2019 - Olugbemi, Victoria Kikelomo; Omoniyi, Mary Banke Iyabo (NIU Journal of Social Sciences, 2021)
After decades of the ratification of the Convention for Elimination of All Forms of Discrimination Against Women (CEDAW), an international treaty which Nigeria signed on 23 rd April, 1984 and ratified on 13 th June 1985, the number of women elected to the three-tier of government in the Federal Republic of Nigeria was very insignificant during the 2015 election. This paper, therefore, examines the impact of CEDAW on the political development of Women in Nigeria from 1985 when Nigeria ratified it. The methodology adopted involves the use of phenomenology, primary and secondary sources for this research. The findings reveal that the twelve key critical areas of CEDAW served as stimulus for women to agitate for non-discrimination, state obligation and substantive gender equality, it however, did not improve their lot. Therefore, the way forward is that women should advocate and lobby for legislation in the domestication of CEDAW before the next election in 2023. Keywords: Rights, International Treaty, Non-Discrimination, Legislation, Domestication.